A novel tissue inhibitor of metalloproteinase-1 (TIMP-1) polymorphism associated with asthma in Australian women. Issue 8 (1st August 2005) - Lose, F; Thompson, P J; Duffy, D; Stewart, G A; Kedda, M-A
Abstract : Background: Airway remodelling is a characteristic feature of chronic asthma and there is evidence that an airway imbalance between levels of matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinases-1 (TIMP-1) is associated with airway remodelling. On this basis, we hypothesised that polymorphisms in the MMP-9 and TIMP-1 genes were associated with the disease process. Methods: A number of MMP-9 and TIMP-1 gene polymorphisms were examined in an adult white Australian population of mild (n = 259), moderate (n = 213) and severe (n = 71) asthmatics and non-asthmatic controls (n = 406) using PCR-RFLP and PCR-SSCP analyses. Results: MMP-9 –1562C>T and 836G>A (Arg279Gln) were not associated with asthma (p⩾0.15) or asthma severity (p⩾0.13), and TIMP-1 434T>C (Phe124Phe) was not associated with asthma in women (p = 0.094) or men (p = 0.207). In this population, MMP-9 −861C>T and TIMP-1 323C>T (Pro87Pro) were not informative (with minor allele frequencies of <1%), and MMP-9 –1702T>A and TIMP-1 595C>T (Ser178Phe) were not detectable. However, a novel polymorphism was detected in the TIMP-1 gene 536C>T (Ile158Ile) which was significantly associated with asthma in women (p = 0.011; OR = 5.54, 95% CI 1.66 to 34.4) but not in men (p = 1.0). 536C>T was found to be in linkage disequilibrium with 434T>C, and haplotype analysis supported an association with asthma (p = 0.014). Conclusions: This is the first reported association between a polymorphism in the TIMP-1 gene and asthma, and supports the hypothesis that the protease/antiprotease balance has an important role in this common disease.